Numerical Simulation of LVAD Inflow Cannulas with Different Tip - Guang-Mao Liu; Hai-Bo Chen; Fu-Liang Luo; Yan Zhang; Han-Song Sun; Jian-Ye Zhou; Sheng-Shou Hu (International Journal of Chemical Engineering)
The tip structure of LVAD inflow cannula is one of major factors to lead adverse events such as thrombosis and suction leading to obstruction. In this research, four kinds of tips that had been used in inflow cannulas were selected and designed. The flow field of the four inflow cannulas inserted into the apex of left ventricle (LV) was numerically computed by computational fluid dynamics. The flow behavior was analyzed in order to compare the blood compatibility and suction in left ventricle and cannulas after the inflow cannulas with different tips were inserted to the apex of LV. The results showed that the cannula tip structure affected the LVAD performance. Among these four cannulas, the trumpet-tipped inflow cannula owned the best performance in smooth flow velocity distribution without backflow or low-velocity flow so that it was the best in blood compatibility. Nevertheless, the caged tipped cannula was the worst in blood compatibility. And the blunt-tipped and beveled tipped inflow cannulas may obstruct more easily than trumpet and caged tipped inflow cannulas because of their shape. The study indicated that the trumpet tip was the most preferable for the inflow cannula of long-term LVAD.